Effects on cigarette consumption of a work–family supportive organisational intervention: 6-month results from the work, family and health network study. Issue 12 (25th May 2016) - Hurtado, David A; Okechukwu, Cassandra A; Buxton, Orfeu M; Hammer, Leslie; Hanson, Ginger C; Moen, Phyllis; Klein, Laura C; Berkman, Lisa F
Abstract : Background: Observational studies have linked work–family issues with cigarette consumption. This study examined the 6-month effects on cigarette consumption of a work–family supportive organisational intervention among nursing home workers. Methods: Group randomised controlled trial where 30 nursing homes across New England states were randomly assigned to either usual practice or to a 4-month intervention aimed at reducing work–family conflict via increased schedule control and family supportive supervisory behaviours (FSSB). Cigarette consumption was based on self-reported number of cigarettes per week, measured at the individual level. Results: A total of 1524 direct-care workers were enrolled in the trial. Cigarette consumption was prevalent in 30% of the sample, consuming an average of 77 cigarettes/week. Smokers at intervention sites reduced cigarette consumption by 7.12 cigarettes, while no reduction was observed among smokers at usual practice sites (b=−7.12, 95% CI −13.83 to −0.40, p<0.05) (d=−0.15). The majority of smokers were US-born White nursing assistants, and among this subgroup, the reduction in cigarette consumption was stronger (b=−12.77, 95% CI −22.31 to −3.22, p<0.05) (d=−0.27). Although the intervention prevented a decline in FSSB (d=0.08), effects on cigarette consumption were not mediated by FSSB. Conclusions: Cigarette consumption was reduced among smokers at organisations where a work–family supportive intervention was implemented. This effect, however, was not explained by specific targets of the intervention, but other psychosocial pathways related to the work–family interface. Trial registration number: NCT02050204; results.